Melatonin reduces hypoxic-ischaemic (HI) induced autophagy and apoptosis: An in vivo and in vitro investigation in experimental models of neonatal HI brain injury. (13th July 2017) - Hu, Yingying; Wang, Zhouguang; Liu, Yanlong; Pan, Shulin; Zhang, Hao; Fang, Mingchu; Jiang, Huai; Yin, Jiayu; Zou, Shuangshuang; Li, Zhenmao; Zhang, Hongyu; Lin, Zhenlang; et al.
Abstract: Melatonin has neuroprotective effects in many diseases, including neonatal hypoxic-ischaemic (HI) brain injury. The purpose of this study was to evaluate the neuroprotective effects of melatonin both in vivo and in vitro and associated molecular mechanisms behind these effects. Postnatal day 7 male and female rat pups were subjected to unilateral HI, melatonin was injected intraperitoneally 1 h before HI and an additional six doses were administered at 24 h intervals. The pups were sacrificed at 24 h and 7 d after HI. Pre-treatment with melatonin significantly reduced brain damage at 7 d after HI, with 15 mg/kg melatonin achieving over 30% recovery in tissue loss compared to vehicle-treated animals. Autophagy and apoptotic cell death as indicated by autophagy associated proteins, cleaved caspase 3 and Tunel staining, was significantly inhibited after melatonin treatment in vivo as well as in PC12 cells. Melatonin treatment also significantly increased the GAP43 in the cortex. In conclusion, melatonin treatment reduced neonatal rat brain injury after HI, and this appeared to be related to inhibiting autophagy as well as reducing apoptotic cell death.